Statistical abstract for East Pakistan : Containing statistical data on various subjects for the years 1950-51 to 1959-60, vol. 4 - Government of East Pakistan; East Pakistan (Pakistan). Bureau of Commercial and Industrial Intelligence; East Pakistan (Pakistan). Provincial Statistical Board (Dacca : East Pakistan Bureau of Statistics, 1964)
"Containing statistical data on various subjects for the years ... to ... (wherever available)."
Vol. 3 is a revised and enlarged issue of its second edition. Cf. Preface, vol. 3.
Includes revised editions numbered consecutively with the original issue.
Keywords: Bangladesh -- Statistics -- Periodicals